Fruit transportation life prediction method and system - GUO YURONG; HUANG XUE; MENG YONGHONG; SONG SHUJIE (2021)
The invention discloses a fruit transportation life prediction method and system. The method comprises the following steps: collecting the fruit damage area, vibration stress and other data of fruits with consistent maturity and size through a transportation vibration damage test system, determining the damage area threshold value according to the current fruit commodity/grading standard, fitting and verifying a fruit vibration stress-transport life (S-N) model, and predicting the transport life of the fruit by using fitting parameters and a transport vibration stress threshold. The method can fill the blank of fruit transportation life prediction methods and systems, and provides theoretical and technical bases for analyzing fruit transportation vibration damage behaviors and formulating preventive loss strategies. 本发明公开了一种水果运输寿命预测方法及系统，对成熟度及尺寸较为一致的水果，利用运输振动损伤测试系统，采集其水果损伤面积及振动应力等数据，根据现行水果商品/分级标准决定其损伤面积阈值，拟合水果振动应力-运输寿命(S-N)模型并验证，利用拟合参数及运输振动应力阈限，预测其运输寿命。该方法可填补水果运输寿命预测方法与系统的空白，为分析水果运输振动损伤行为及制定预防性减损策略的提供理论与技术基础。